2002
DOI: 10.1021/ja017052o
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Hydraphile Channels of Appropriate Length Kill Escherichia coli

Abstract: Crown ether-based synthetic cation conducting channels called hydraphiles show clear ionophoretic activity in phospholipid vesicles. These compounds are shown to be active against the bacterium E. coli. Disk diffusion assays were performed to assess the toxicity of different hydraphile derivatives. Liquid culture tests were conducted to quantitate the dependence of bacterical activity on channel length. It is proposed that hydraphiles are toxic to bacteria as a result of channel formation in the membrane. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(96 citation statements)
references
References 21 publications
4
92
0
Order By: Relevance
“…The results from the simulations provided details about the hydraphile-membrane interactions and confirmed that hydraphiles with the appropriate length of the alkyl chain linkers between the crown-ether moieties adopt a membrane-spanning conformation. The resulting picture is consistent with a membrane-spanning model proposed by Leevy et al [242].…”
Section: Protein Insertion Into Membranessupporting
confidence: 91%
“…The results from the simulations provided details about the hydraphile-membrane interactions and confirmed that hydraphiles with the appropriate length of the alkyl chain linkers between the crown-ether moieties adopt a membrane-spanning conformation. The resulting picture is consistent with a membrane-spanning model proposed by Leevy et al [242].…”
Section: Protein Insertion Into Membranessupporting
confidence: 91%
“…[6][7][8][9]12 These channels show open-shut behavior characteristic of protein channels. They exhibit selectivity for cations over anions and for Na + over K + .…”
Section: Use Of Hydraphiles As a Membrane Probementioning
confidence: 99%
“…E. coli are small (~0.5×2 µm), but they are readily detectable by optical microscopy. The suspension above was examined with a fluorescent microscope and fluorescence was clearly identified in the periphery of the organism and not within it to any significant extent [20]. This is illustrated in Figure 5.…”
Section: Resultsmentioning
confidence: 98%
“…Ion concentrations are closely regulated in all vital cells, even in the simplest microbes. We reasoned, and later demonstrated [19], that hydraphiles can insert in microbial membranes [20]. If so, they should disrupt the natural ion balance (ion homeostasis) of these organisms, potentially with toxic effect.…”
Section: Resultsmentioning
confidence: 99%